2021
DOI: 10.3390/biom11050704
|View full text |Cite
|
Sign up to set email alerts
|

Into the Deep: New Data on the Lipid and Fatty Acid Profile of Redfish Sebastes mentella Inhabiting Different Depths in the Irminger Sea

Abstract: New data on lipid and fatty acid profiles are presented, and the dynamics of the studied components in muscles in the males and females of the beaked redfish, Sebastes mentella, in the depth gradient of the Irminger Sea (North Atlantic) is discussed. The contents of the total lipids (TLs), total phospholipids (PLs), monoacylglycerols (MAGs), diacylglycerols (DAGs), triacylglycerols (TAGs), cholesterol (Chol), Chol esters, non-esterified fatty acids (NEFAs), and wax esters were determined by HPTLC; the phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The low percentage similarity between S. beanii and other mesopelagic fishes in the study may be due to a greater exogenous supply of EPA since this acid, together with some MUFAs, is plentiful in Arctic hyperiid amphipods [102]. Similar build-up of EPA and DHA towards greater depths has been described in our previous studies on beaked redfish [75].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The low percentage similarity between S. beanii and other mesopelagic fishes in the study may be due to a greater exogenous supply of EPA since this acid, together with some MUFAs, is plentiful in Arctic hyperiid amphipods [102]. Similar build-up of EPA and DHA towards greater depths has been described in our previous studies on beaked redfish [75].…”
Section: Discussionsupporting
confidence: 62%
“…A significant effect on the processes of lipid storage, transfer, and transformation is produced also by the dietary specializations of fishes [70,71]. The depth-related differences in TL accumulation detected in our study possibly point to differences in the diets and foraging rates, as well as to an overall reduction in food availability at high depths [24,[72][73][74][75].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, such changes may serve as a potential indicator of the environment and habitat of different fish species. Voronin et al [ 58 ] reported phospholipid contents in the range of 0.23% to 2.14% DW in beaked redfish ( Sebastes mentella ) obtained from different depth levels in the Irminger sea. Furthermore, they documented a negative correlation between phospholipid fractions (phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, and phosphatidylinositol) and the depth at which the fish were located.…”
Section: Factors Affecting Phospholipid Compositionmentioning
confidence: 99%
“…For example, farmed small and large-size Bouri Fish ( Mugil cephalus ) collected from a fish farm at Kafr El-Sheikh in Egypt were reported to have a different phospholipid content, ranging from 1.04 to 3.56% of the lipid content, respectively [ 59 ]. Additionally, Voronin, Nemova, Ruokolainen, Artemenkov, Rolskii, Orlov, and Murzina [ 58 ] reported variations in the number of total phospholipids (0.44–2.14 and 0.23–1.39% DW), major (phosphatidylcholine (0.76–1.6% and 0.16–0.98% DW) and phosphatidylethanolamine (0.12–0.53% and 0.06–0.28% DW)), minor (lysophosphatidylcholine (0.04–0.09 and 0.01–0.07% DW), phosphatidylinositol (0.01–0.06 and 0.003–0.05% DW), and phosphatidylserine (0.01–0.02 and 0.002–0.02% DW) phospholipid fractions between male and female beaked redfish ( Sebastes mentella ), respectively. Moreover, Drazen [ 55 ] reported significant ( p > 0.05) differences in the contents of lysophosphatidylcholine, phosphatidylethanolamine, and phosphatidylserine in the muscles of wild and farmed beaked redfish.…”
Section: Factors Affecting Phospholipid Compositionmentioning
confidence: 99%
“…Voronin et al [ 9 ] explored lipids and fatty acids in muscles of beaked redfish, Sebastes mentella , in a depth gradient. At all depths, high contents of DHA and EPA were observed in the redfish muscles, which was supposed to be the species’ trait.…”
mentioning
confidence: 99%